The feminist avant-garde in American poetry - Frost, Elisabeth A. (Elisabeth Ann), 1963- (Iowa City : University of Iowa Press, 2003)
The Feminist Avant-Garde in American Poetry offers a historical and theoretical account of avant-garde women poets in America from the 1910s through the 1990s and asserts an alternative tradition to the predominantly male-dominated avant-garde movements. Elisabeth Frost argues that this alternative lineage distinguishes itself by its feminism and its ambivalence toward existing avant-garde projects; she also thoroughly explores feminist avant-garde poets' debts and contributions to their male counterparts. --
Part I. Women Poets and the Historical Avant-Gardes. -- "Replacing the Noun": Fetishism, Parody, and Gertrude Stein's Tender Buttons -- "Crisis in Consciousness": Mina Loy's "Anglo-Mongrels and the Rose" -- Part II. Agendas of Race and Gender. -- "a fo / real / revolu/shun": Sonia Sanchez and the Black Arts Movement -- Part III. Traditions of Marginality. -- "Unsettling" America: Susan Howe and Antinomian Tradition -- "Belatedly Beladied Blues": Hybrid Traditions in the Poetry of Harryette Mullen.
Includes bibliographical references (pages 209-225) and index.
Print version record.
JSTOR
Keywords: American poetry -- 20th century -- History and criticism; Feminism and literature -- United States -- History -- 20th century; Avant-garde (Aesthetics) -- United States -- History -- 20th century; Women and literature -- United States -- History -- 20th century; American poetry -- Women authors -- History and criticism; Experimental poetry, American -- History and criticism; Feminist poetry, American -- History and criticism; Poésie américaine -- 20e siècle -- Histoire et critique; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Poésie expérimentale américaine -- Histoire et critique; Poésie féministe américaine -- Histoire et critique; LITERARY CRITICISM -- Poetry; SOCIAL SCIENCE -- Women's Studies; American poetry; American poetry -- Women authors; Avant-garde (Aesthetics); Experimental poetry, American; Feminism and literature; Feminist poetry, American; Women and literature; United States; Frauenlyrik; Feminismus; Avantgarde; USA; 1900-1999; Geschichte 1910-2000.; Electronic books; Criticism, interpretation, etc; History